Id4 functional analysis during neurogenesis using zebrafish as a model organism - Girayer, Elif Naz (2017)
Id4 is a member of Id proteins which belong to a transcription factor family called “basic helix-loop-helix (bHLH)”proteins. bHLH family members contain a DNA binding domain and a helix-loop-helix domain that enables dimerisation between bHLH proteins. Id proteins are not capable of DNA binding due to absence of basic (DNA binding) domain. Therefore Id-bHLH heterodimerisation results in inhibition of bHLH activity which drives cellular differentiation. Id4 plays an important role in proliferating cells maintaining neural stem cell pool and controlling the timing of differentiation as well as apoptosis in the mouse. TALEN-mediated knockout of Id4 in zebrafish resulted in a reduction of Sox2 expression a marker for neural stem cells suggesting a reduction of the stem cell pool. In addition, premature GFAP expression a marker of astrocytes suggests that reduction of thestem cells pool is in part due to premature glial differentiation. HuC expression marking neurons was not changed however at 24 hpf. The observed phenotype was similar to that exhibited in mutants of the notch signalling pathwaysuggesting that Id4 could be a downstream target of notch. Indeed, Id4 expression was elevated in mind bomb mutants and embryos treated with DAPM an inhibitor of the notch signalling pathway suggesting that notch negatively regulates Id4 expression.